War & peace [videorecording (DVD)] : the complete miniseries - James, Lily, 1989-; Dano, Paul, 1984-; Norton, James, 1985- (Anchor Bay Entertainment, 2016)
A modern take on one of the most famous stories of all time. In 1805 when we first meet Pierre, Natasha, and Andrei, they are all part of St. Petersburg's glittering elite, but are fired up with youthful ambition to find meaning in their lives. As everything they thought they knew is questioned, Pierre, Andrei and Natasha find themselves in a time when Russian society is about to change forever.